Peningkatan Kemampuan Berhitung Siswa melalui Media Manipulatif di SD Negeri 020 Teluk Pulau Hilir Kecamatan Rimba Melintang - Ernawati; Susanti, Meri; Solihin, Solihin (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Numeracy is an important basic skill for primary school students to support mathematics learning and daily life. However, many students at SD Negeri 020 Teluk Pulau Hilir experience difficulties in understanding counting concepts due to the lack of varied learning methods. Teachers still dominantly use conventional approaches such as lectures and practice problems, making it less interesting for students. This study aims to improve the counting skills of low grade students through the application of manipulative media. This research uses the Classroom Action Research (PTK) method which consists of planning, implementation, observation, and reflection in two cycles. Data was collected through observation, interviews, and tests before and after the application of manipulative media. The results showed that the use of manipulative media significantly improved students’ understanding of counting concepts. Students were more enthusiastic in learning, more active in discussions, and able to complete counting operations more quickly and accurately. Teachers are also more creative in teaching and creating interactive learning. In conclusion, manipulative media is effective in improving students’ counting skills. Therefore, this method is recommended to be applied in learning mathematics to improve students’ motivation and learning outcomes..